Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
ancao
Xem chi tiết
Nguyễn Lê Phước Thịnh
28 tháng 8 2021 lúc 20:08

\(9x^2+6xy+y^2-25\)

\(=\left(3x+y\right)^2-25\)

\(=\left(3x+y-5\right)\left(3x+y+5\right)\)

Hồng Phúc
28 tháng 8 2021 lúc 20:08

\(9x^2+6xy+y^2-25=\left(3x+y\right)^2-25=\left(3x+y-5\right)\left(3x+y+5\right)\)

Phạm Trần Hoàng Anh
28 tháng 8 2021 lúc 20:09

9x2+6xy+y2-25= (3x)2+2.3x.y+y2 -25

                        = (3x+y)2-52

                        = (3x+y-5).(3x+y+5)

Học tốt!

Yunn
Xem chi tiết
Akai Haruma
8 tháng 10 2023 lúc 20:06

Lời giải:

a. $A=9x^2+15x+6xy+y^2+5y=(9x^2+6xy+y^2)+(15x+5y)$
$=(3x+y)^2+5(3x+y)=0^2+5.0=0$

b. $25x^2-y^4-5x+y^2=(25x^2-y^4)-(5x-y^2)=(5x-y^2)(5x+y^2)-(5x-y^2)$

$=(5x-y^2)(5x+y^2-1)$

THẢO HUỲNH THỊ THU
Xem chi tiết
๖ۣۜHả๖ۣۜI
11 tháng 11 2021 lúc 11:59

(9x2-6xy+y2)-42

=(3x-y)2-42

=(3x-y-4)(3x-y+4)

Nguyễn Việt Lâm
11 tháng 11 2021 lúc 19:31

\(=\left(9x^2-6xy+y^2\right)-2^2\)

\(=\left(3x-y\right)^2-2^2\)

\(=\left(3x-y-2\right)\left(3x-y+2\right)\)

ngtt
Xem chi tiết

\(a,4x^2+28x+49=\left(2x\right)^2+2.2x.7+7^2=\left(2x+7\right)^2\\ b,16y^2-8y+1=\left(4y\right)^2-2.4y.1+1^2=\left(4y-1\right)^2=\left(1-4y\right)^2\\ 4a^2+20ab+25b^2=\left(2a\right)^2+2.2a.5b+\left(5b\right)^2=\left(2a+5b\right)^2\\ d,9x^2-6xy+y^2=\left(3x\right)^2-2.3x.y+y^2=\left(3x-y\right)^2=\left(y-3x\right)^2\)

Yến Nhyy
Xem chi tiết
Lấp La Lấp Lánh
21 tháng 9 2021 lúc 18:04

a) \(16x^2+8xy+y^2=\left(4x+y\right)^2\)

b) \(4x^2-2xy+\dfrac{1}{4}y^2=\left(2x-\dfrac{1}{2}y\right)^2\)

c) \(x^2+x+\dfrac{1}{4}=\left(x+\dfrac{1}{2}\right)^2\)

d) \(9x^2-6xy+y^2=\left(3x-y\right)^2\)

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
21 tháng 1 2017 lúc 13:39

tanqr
Xem chi tiết
Lấp La Lấp Lánh
5 tháng 10 2021 lúc 19:04

a) \(=\left(6x\right)^2-2.6x.1+1=\left(6x-1\right)^2\)

b) \(=5xy\left(x^2+2x+1\right)=5xy\left(x+1\right)^2\)

c) \(=\left(3x-y\right)^2-25=\left(3x-y-5\right)\left(3x-y+5\right)\)

d) \(=x\left(x+1\right)+7\left(x+1\right)=\left(x+1\right)\left(x+7\right)\)

이성경
Xem chi tiết
Trần Nguyễn Bảo Quyên
18 tháng 9 2017 lúc 18:26

\(1.\)

\(a.\)

\(\left(x-3\right)\left(x^2+3x+9\right)-\left(54+x^3\right)\)

\(=\left(x^3-3^3\right)-\left(54+x^3\right)\)

\(=x^3-27-54-x^3\)

\(=-81\)

\(b.\)

\(\left(3x+y\right)\left(9x^2-3xy+y^2\right)-\left(3x-y\right)\left(9x^2+3xy+y^2\right)\)

\(=\left(27x^3+y^3\right)-\left(27x^3-y^3\right)\)

\(=27x^3+y^3-27x^3+y^3\)

\(=2y^3\)

\(2.\)

\(a.\)

\(\left(x+3y\right)\left(x^2-3xy+9y^2\right)=x^3+27y^3\)

\(b.\)

\(\left(2x-3y\right)\left(4x^2+6xy+9y^3\right)=8x^3-27y^3\)

Trang
18 tháng 9 2017 lúc 18:28

1) a) \(\left(x-3\right)\left(x^2+3x+9\right)-\left(54+x^3\right)\)

\(=\left(x^3-3^3\right)-\left(54+x^3\right)\\ =\left(x^3-27\right)-54-x^3\\ =-27-54\\ =-81\)

b) \(\left(3x+y\right)\left(9x^2-3xy+y^2\right)-\left(3x-y\right)\left(9x^2+3xy+y^2\right)\)

\(=\left[\left(3x\right)^3+y^3\right]-\left[\left(3x\right)^3-y^3\right]\\ =2y^3\)

2) a) \(\left(x+3y\right)\left(x^2-3xy+9y^2\right)=x^3+27y^3\)

b) \(\left(2x-3y\right)\left(4x^2+6xy+9y^2\right)=8x^3-27y^3\)

Nguyễn Ngọc
Xem chi tiết
trần khánh linh
Xem chi tiết
Nguyễn Hoàng Minh
7 tháng 10 2021 lúc 18:19

\(a,=\left(x+1\right)^2\\ b,=\left(3x-y\right)^2\\ c,=\left(x-3\right)\left(x+3\right)\\ d,=\left(x+4\right)^3\\ e,=\left(x-2\right)^3\\ f,=\left(x+2\right)\left(x^2-2x+4\right)\\ g,=\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)